Development of an HPLC Method for Simultaneous Quantitation of Hyperin, Quercetin and Kaempferol in the Semen cuscutae - Thi Dinh, Do; Thi Minh Diep, Nguyen; Anh, Tran Thi Van; Thanh Hoa, Ha; Viet Hung, Dao; Thi Xuan Thinh, Ngo; Thanh Hai, Nguyen; Quoc Tuan, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
In this study, a method for the simultaneous quantification of hyperin, quercetin, and kaempferol in samples of S emen cuscutae was developed using high-performance liquid chromatography (HPLC). The chosen chromatographic conditions were a mobile phase of methanol – 0.1% formic acid in water, running in gradient mode, with a flow rate of 0.9 mL/min, and detection wavelengths of 354, 365, and 369 nm for hyperin, kaempferol, and quercetin, respectively. The results of the quantitative analysis of 5 samples of S emen cuscutae purchased from Phu Tho province showed hyperin content ranging from 0.950 to 1.218 mg/g, quercetin from 0.077 to 0.118 mg/g, and kaempferol from 1.051 to 1.190 mg/g based on the dry weight of the medicinal material. This research may be suitable for the quality control of S emen cuscutae in the market.